Monitoramento da qualidade do ar de ambientes internos: bibliotecas - Ito, Lissandra Xavier (2007)
The main objective of this study was to monitor and to characterize the particulate material (PM) with equivalent diameter between 2,5 and 10 µm (PM2,5-10), particulate with equivalent diameter smaller than 2,5 µm (PM2,5), particulate with total suspended particles (TSP), and some pollutant gases (ammonia, chlorine, carbon dioxide, ozone, benzene, carbon monoxide and toluene) presents in the indoor environments of public Libraries. Two libraries located in the city of São Paulo were chosen, the Chemistry Buildings Library of the University of São Paulo (CQ USP), and the Library Monteiro Lobato, and two libraries located in the city of São Carlos, the Library Amadeu Amaral and the Communitarian Library of the Federal University of São Carlos (UFSCar). It was used a Small Volume Sampler (APV) which captured the particles using a glass fibre filter and nuclepore hydrophobic membranes, and a chip monitoring system (CMS) which measured the gases concentrations. The experimental essays were followed in the indoor and outdoor environments of the libraries, working with a flow of 16 L/min and sampling time of 1 hour, once a week, varying in relation to the day of the week and the schedule of sampling. After the collection, analyses of X-Ray Fluorescence (XRF) were done to quantify the chemical elements with atomic number superior of 13 g/mol. The chemical elements found in the particulate material of those indoor environments were: Al, Ca, Fe, Cu, Br, Rb, Cl, K, Ti, V, Sr, and S. The results showed that the particulate concentrations between PM2.5-10 and PM2.5 in the indoor environments of the libraries were always greater than in the outdoor ones. The Libraries located downtown São Paulo and São Carlos (Amadeu Amaral and Monteiro Lobato) presented greater concentrations of indoor particulate in the two fractions, PM2.5 and PM2.5-10, justified by the pollution of vehicles, industries, soil resuspension and burning of sugarcane.